The Influence of Agrosilvopasture Implementation and MSME Incubation on SDGs in Rural Areas of Indonesia with Financial Literacy as a Mediator - Ariyanti, Indri; Mayasari, Riana; Febriantoko, Jovan; Harbi, Jun; Prima, Fidel Harmanda; Lidya, Desti; Masnila, Nelly; Sunardi, - (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2024)
This study aimed to explore the roles of Agrosilvopasture, MSME (Micro, Small, and Medium Enterprise) Incubation, and financial literacy in supporting Sustainable Development Goals (SDGs) in rural areas of Indonesia. The study procedures were carried out from April to September 2023 in Pagar Alam City using indigenous communities and stakeholders associated with customary forest management, comprising 100 intentionally selected respondents. Subsequently, the Slovin formula was used to determine the number of respondents, who were then selected using a purposive sampling method. The relationships among variables, including Implementation of Agrosilvopasture (X1), MSME Incubation (X2), Financial Literacy (M), and SDGs (Y), were tested. Data obtained were then analyzed using the Partial Least Squares-SmartPLS. The results of path coefficient analysis showed that Agrosilvopasture had a significant negative influence on financial literacy but a positive impact on SDGs. In addition, MSME incubation yielded a favorable impact on both financial literacy and SDGs. Mediation testing validated that financial literacy served as a mediator in the relationship between Agrosilvopasture and the examined outcomes. Based on the results, financial literacy, Agrosilvopasture implementation, and MSME incubation were crucial for achieving SDGs in rural areas. These holistic approaches offered promising pathways to achieve various SDGs, with financial literacy playing an essential role in enhancing the effectiveness of the strategies.